Trends in the Development of Investment Processes in Uzbekistan - Musabekov Ulugbek Jorobekovich (European Science Publishing, 2023)
This article discusses the main directions of development of investment processes in the Republic of Uzbekistan. One of the important factors of economic growth is the formation of an investment strategy to modernize the branches of the real sector of the national economy.
Keywords: national economy, investments, strategy, structure, investment processes, capital, competitive potential, authorities, investment environment, investment policy.